Diksi Dan Gaya Bahasa Pada Cerkak Sindhen Karya Andjar Any Kajian Stilistika - Hasan, Imadul Bilad; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2022)
The purpose of this paper is to find out the style of language and diction in the Sindhen story by Andjar Any. Cerkak is one of the literary works that is included in the type of prose literary work. The absolute characteristic in literary works is the beauty, authenticity and artistic value in its content and expression. A work cannot be said to be a literary work if one of these elements is not fulfilled. Cerkak is similar to short stories or short stories, because cerkak is an abbreviation of "stories of short stories". In other terms, it is often referred to as a short story. One of the stories that will be studied is the Sindhen script by Andjar Any. This study uses a qualitative descriptive method with stylistic studies to analyze the linguistic system in the form of diction and language style in the geguritan. The data used in this study are words, sentences, and quotes on Cerkak Sindhen. In writing the Sindhen story, he uses a variety of languages so that the contents of the story are more interesting to read. The results of this research found Diction and Language Style contained in the Javanese Short Story entitled Sindhen by Andjar Any. The diction found in the cerkak are (1) denotative meaning (2) connotative meaning, (3) synonym, (4) antonym. Meanwhile, the language styles found are (1) comparative language style, (2) affirmation language style, (3) language style and (4) satire language style.